Hubungan Perilaku 3M Plus dengan Kejadian Demam Berdarah Dengue (DBD) - Supriyadi Periatama; Rizki Muji Lestari; Dita Wasthu Prasida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Dengue Hemorrhagic Fever (DHF) has a fast course and is often fatal because there are still many patients who die due to late treatment. The phenomenon of cases of Dengue Hemorrhagic Fever (DHF) in Central Kalimantan Province was reported to have 1,786 cases, more when compared to the number of cases of Dengue Hemorrhagic Fever (DHF) in 2018 as many as 2,222 cases, with the number of deaths in 2019 as many as 44 people, lower if compared to the number of deaths in 2018 as many as 22 people. The purpose of this study was to determine the